Nonclinical safety assessment of repeated administration and biodistribution of ChAd3‐EBO‐Z Ebola candidate vaccine. Issue 6 (21st January 2020) - Planty, Camille; Chevalier, Guillaume; Duclos, Marie‐Ève; Chalmey, Clémentine; Thirion‐Delalande, Catherine; Sobry, Cécile; Steff, Ann‐Muriel; Destexhe, Eric
Abstract: ChAd3‐EBO‐Z is an investigational adenovirus‐based vaccine for the prevention of Ebola virus disease. Two nonclinical studies were performed to evaluate the biodistribution, local tolerance and potential local and systemic toxic effects of this vaccine. In the biodistribution study, rats received a single intramuscular injection of either ChAd3‐EBO‐Z or saline. Enlargement of the draining lymph nodes, starting on day 2, was noticed in ChAd3‐EBO‐Z‐treated rats, indicating that an immune response had taken place. Viral DNA was mainly found at the injection sites and in the draining lymph nodes, from where it progressively disappeared during the observation period, while it was found only transiently and occasionally in other organs. In the repeated‐dose toxicity study, either ChAd3‐EBO‐Z or saline was administered intramuscularly to rabbits on two occasions with a 2‐week interval. General health status, rectal temperature, local tolerance, ophthalmology, hematology, coagulation and blood chemistry parameters were monitored. Macroscopic and microscopic evaluations were performed. Treatment‐related changes included a transient increase in neutrophil count, C‐reactive protein and fibrinogen levels, and a transient decrease in platelet count. As expected, microscopic observations 3 days after the second injection were related to the elicited inflammatory reaction, and these inflammatory responses had almost completely disappeared 29 days after the second immunization. In conclusion, the vaccine was locally and systemically well‐tolerated and the viral vector was partially or totally cleared from the organs where it disseminated, supporting the clinical development of the vaccine. Abstract : ChAd3‐EBO‐Z is an investigational vaccine for the prevention of Ebola virus disease. The local tolerance and the potential local and systemic effects of this vaccine were evaluated in rabbits and its biodistribution in rats. The vaccine was locally and systemically well‐tolerated and the viral vector was partially or totally cleared from the few organs where it disseminated, thus supporting the clinical development of the vaccine.